2006
DOI: 10.2134/jeq2005.0093
|View full text |Cite
|
Sign up to set email alerts
|

Diuron in Surface Runoff and Tile Drainage from Two Grass‐Seed Fields

Abstract: The typical method of cool-season grass-seed production in Mediterranean climates briefly exposes surface waters to potentially high concentrations of the herbicide diuron [3-(3,4-dichlorophenyl)-1,1-dimethyl urea] during the initial season of growth. To better understand the process, and the degree, of diuron transport from agricultural fields, two grass-seed fields in the Willamette Valley of Oregon were monitored for diuron loss in surface runoff and tile drainage during the first wet season after planting.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Biotic processes of soil degradation also influenced the speciation of compounds in the runoff by the evidence of diuron and DCPMU as the largest loadings in the two runoff events. The absence of diuron in runoff during the second event was consistent with other field runoff studies, where, under shorter timeframes, its diminution in runoff approached concentrations of 1 µg L −1 7–9. DCMPU showed a large temporal increase in runoff concentration that was not consistent with trends for diuron.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Biotic processes of soil degradation also influenced the speciation of compounds in the runoff by the evidence of diuron and DCPMU as the largest loadings in the two runoff events. The absence of diuron in runoff during the second event was consistent with other field runoff studies, where, under shorter timeframes, its diminution in runoff approached concentrations of 1 µg L −1 7–9. DCMPU showed a large temporal increase in runoff concentration that was not consistent with trends for diuron.…”
Section: Discussionsupporting
confidence: 86%
“…By the average concentrations of detected compounds and total volumes in the runoff events, their estimated total loadings were 2.6% of applied diuron. Other studies calculated maximum losses of applied diuron that were between 0.7 and 1.7% in cultivated and uncultivated blocks of vineyard,7 between 1.3 and 3% under perennial pasture production8 and 2.2% from a mixed agricultural catchment 10. The application of diuron in the sugarcane farming catchments of coastal Queensland was estimated as 197 000 kg diuron ha −1 year −1 in 1996 18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Revitt et al [6] detected concentrations of this compound as high as 238.4 mg L −1 in urban runoff after a storm event. Determination of herbicides in highway runoff showed diuron concentration up to 10.78 mg L −1 [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Many works were devoted to study of pesticide leaching process in soil. It was demonstrated that leaching behavior of pesticides depends on irrigation or rainfall amounts and their time distribution, chemical characteristics of pesticide and properties of soil [15][16][17][18] . According to Tiktak with co-authors (2012), leaching of pesticides can be linked with soil macropore system which, in its turn, is connected with organic matter and clay content 19 .…”
mentioning
confidence: 99%